Ecological dynamics of Aedes mosquitoes: unraveling the impact of larval competition and temperature on dengue transmission (2025)
This study investigates how temperature variability and larval competition influence Dengue transmission dynamics in systems where Aedes aegypti and Aedes albopictus coexist. We developed a deterministic model incorporating temperature-dependent parameters to analyze vector interactions across larval and adult stages, coupled with a SEIR framework for human infection dynamics. Using Pairwise Invasibility Plots, coexistence analysis, and infection peak assessment, we evaluated species invasion capability, population dynamics, and disease transmission patterns. Results showed that temperature enables Ae. albopictus invasion even under high interspecific competition ($>$70%), contrasting with its limited invasion capacity ($<$40%) in temperature-independent conditions. Coexistence analysis demonstrated that temperature variability promotes balanced relative abundances between species, countering the typical Ae. aegypti dominance observed in stable thermal conditions. Infection analysis revealed unexpected patterns, with highest infection peaks occurring in scenarios combining low larval competition for Ae. aegypti with high competition for Ae. albopictus. These findings challenge traditional assumptions about vector dominance in Dengue transmission and emphasize the importance of temperature-sensitive control strategies in regions where both species coexist under climate change conditions.